2012
DOI: 10.1161/circimaging.112.974907
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Superparamagnetic Particles of Iron Oxide in Patients With Acute Myocardial Infarction

Abstract: Magnetic resonance imaging (MRI) is ideally suited for the serial examination of the heart because it is noninvasive, does not involve ionizing radiation, and has excellent soft tissue contrast and spatial resolution. Cardiac magnetic resonance, using T2-weighted imaging, has previously been used to detect Background-Inflammation following acute myocardial infarction (MI) has detrimental effects on reperfusion, myocardial remodelling, and ventricular function. Magnetic resonance imaging using ultrasmall superp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
111
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 32 publications
1
111
2
Order By: Relevance
“…23 Ferucarbotran and ferumoxides, approved for MRI in the past, were similarly withdrawn from the market. To fulfil the clinical need, the intravenous iron replacement agent ferumoxytol (Feraheme/Rienso, 17-30 nm particles coated with a low-molecular-weight semisynthetic carboxylated polymer) was used as a contrast agent to characterize the myocardial infarct pathology 24,25 and to differentiate simple steatosis from NASH. 26 It must be noted, however, that the required concentrations of ferumoxytol were very high, 4-7.2 mg Fe/kg body weight in myocardial infarct 24,25 and 3.6 mg/kg in patients with liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…23 Ferucarbotran and ferumoxides, approved for MRI in the past, were similarly withdrawn from the market. To fulfil the clinical need, the intravenous iron replacement agent ferumoxytol (Feraheme/Rienso, 17-30 nm particles coated with a low-molecular-weight semisynthetic carboxylated polymer) was used as a contrast agent to characterize the myocardial infarct pathology 24,25 and to differentiate simple steatosis from NASH. 26 It must be noted, however, that the required concentrations of ferumoxytol were very high, 4-7.2 mg Fe/kg body weight in myocardial infarct 24,25 and 3.6 mg/kg in patients with liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several oedema imaging methods exist-single-photon emission computed tomography, [26] T2W CMR, [19] LGE endocardial surface area, [27] T1 mapping CMR, [3,4,23] and T2 mapping CMR[13, 23]-but this study represents the first application of T1 mapping with a quantitative ROC-threshold optimised to a STEMI population. The precedent for such an approach was set by Ferreira et al [28], in a recent study on myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this hypothesis was put forward by other investigators who showed that ultra-small superparamagnetic particles of iron oxide are retained in segments very remote from the infarct. [27] Second, the T1 may have been abnormal in these patients prior to myocardial infarction, due to discrete microscopic fibrosis caused by comorbidities such as diabetes, hypertension or hypercholesterolemia. [30,31] In order to establish which hypothesis is correct, our findings would have to be validated through histology.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic was already shown in clinical trials for myocardial infarction, aortic aneurysms, and carotid plaques. 3,4,50,51 Furthermore, imaging of iron-laden leukocytes during pathologies such as atherosclerosis, stroke, and various types of cancer is a promising field of current preclinical research, as recently reviewed elsewhere. 20 IONs have a high sensitivity in MRI, as concentrations in the nanomolar range can be detected and visualized.…”
mentioning
confidence: 99%